2005
DOI: 10.1007/s11249-004-1748-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of interaction of EP and AW additives with dispersants using XANES

Abstract: The chemical interaction of two kinds of dispersants (bis-succinimide dispersant and borated bis-succinimide dispersant) with four kinds of antiwear (AW) and extreme pressure (EP) additives (zinc dialkyldithiophosphate, dialkyldithiophosphate ester, diphenylphosphate ester and dialkyldithiocarbamate) has been investigated under different contact pressures. The chemical compositions of the tribofilms have been studied by B, N, P and S X-ray absorption near edge structure (XANES) spectroscopy. The N K-edge XANES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…A similar effect is found with tributyl phosphite [24]. While the chemical nature of the phosphorus cannot be measured using Auger spectroscopy, NEXAFS analyses of the tribological films formed from phosphorus-containing additives reveal the formation of phosphates [33][34][35][36][37]. At higher phosphorus concentrations and temperatures, the phosphates polymerize to form relatively hard polyphosphate glasses.…”
Section: Discussionmentioning
confidence: 69%
“…A similar effect is found with tributyl phosphite [24]. While the chemical nature of the phosphorus cannot be measured using Auger spectroscopy, NEXAFS analyses of the tribological films formed from phosphorus-containing additives reveal the formation of phosphates [33][34][35][36][37]. At higher phosphorus concentrations and temperatures, the phosphates polymerize to form relatively hard polyphosphate glasses.…”
Section: Discussionmentioning
confidence: 69%
“…6(a), and the spectral data are listed in Table 1 spectrum correspond to iron sulfide, alkylsulfur, [28] sulfite and sulfate, respectively. It can be seen that temperature has some influence on the components of tribofilms.…”
Section: Xanes Spectroscopy Of Tribofilms At Different Temperaturesmentioning
confidence: 99%
“…[25,28], and the alkyldisulfide comes from the decomposition of the additive molecule. Peak c situated at 2477.0 eV corresponds to sulfite, and peak d situated at 2482.1 eV corresponds to sulfate.…”
Section: S and P K-edge Xanes Spectra Of Thermal Filmsmentioning
confidence: 99%
“…Since its first application in 1989, many papers based on the application of XANES to study ZDDP films have been published [8][9][10][11][12][13][14][15][16]. The interaction of ZDDP with detergents or dispersant has also been investigated widely by many studiers [9,[17][18][19]. Yin et al [9] found that the polyphosphate films formed in the presence of the detergents and dispersants have shorter-chain length compared with ZDDP alone and contain less unchanged ZDDP.…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al [9] found that the polyphosphate films formed in the presence of the detergents and dispersants have shorter-chain length compared with ZDDP alone and contain less unchanged ZDDP. Zhang et al [17][18][19] found that the borated dispersant facilitates the decomposition of ZDDP and the formation of phosphate in tribofilms and thermal films.…”
Section: Introductionmentioning
confidence: 99%